RELASI PEMERINTAH DAERAH DAN SWASTA DALAM PENGELOLAAN DESTINASI WISATA DI KELURAHAN SEI GOHONG - Armela Shintani (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2020)
ABSTRAK Relations or relationships are the result of systematic interactions (series of behaviors) between two or more people that have a reciprocal relationship and influence each other between one individual and another individual. Governance is oriented to the synergic relations (relations) between the government, the private sector and civil society (community) in carrying out good and responsible governance. In other words, the relationship between Regional and Private Governments in the management of tourist destinations shows that there is cooperation/ partnership of stakeholders, namely the government, the private sector and the community. This research method uses descriptive qualitative research. This research uses governance theory from Sumarto. The indicators used include Government indicators as facilitators, Private indicators as providers and service providers and Community indicators as citizens participating in tourism management. This research in the process uses data from observations, interviews and documentation. The results of this study indicate that there is a relationship between the local government, the private sector and the community in managing tourist destinations in Sei Gohong, this can be seen from the interaction of the three stakeholders. The government as a facilitator who facilitates tourism needs, things that have not been met in the provision of tourism services by the government are complemented by the private sector as providers and organizers of tourism services namely accommodation in the form of lodging (villas) and the community in the tourist areas participate by managing Sei Gohong tourism by the Group Tourism Awareness (Pokdarwis). However, the management of these tourist destinations only involves local governments through the Department of Tourism, Culture, Youth and Sports Palangkaraya City together with the community through the Tourism Awareness Group (Pokdarwis) who are directly involved in tourism management in Sei Gohong. While the private sector indirectly as a provider and service provider because of the impact of the presence of tourism.   Keywords: Relations, Governance, Management of Tourism Destinations